PENGARUH PENGEMBANGAN KARIER DAN STRES KERJA TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA PADA KPP PRATAMA BATANG - Suprayitno, Suprayitno; Budiati, Yuli; Indarto, Indarto; Savitri, Fania Mutiara (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
This study purposes to identify the factors that can improve employee performance. The independent variables in this study are career development and job stress, and the dependent variable is performance with job satisfaction as the intervening variable. This study uses a quantitative method using a questionnaire to collect the required data. The sample in this study were 88 KPP Pratama Batang employees. The sampling technique used is simple random sampling. The data analysis method uses regression analysis which is processed using SPSS. The results of this study indicate that Career Development has positive significance effect on Job Satisfaction, Work Stress has negative significance effect on Job Satisfaction, Job Satisfaction has an effect on Employee Performance, Career Development has no effect on Employee Performance, Work Stress has no effect on Employee Performance, Career Development has positive significance effect on Employee Performance mediated by satisfaction work, and work stress affects employee performance mediated by job satisfaction.